2022
DOI: 10.3390/w14213428
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence and Role of Tetrasphaera in Enhanced Biological Phosphorus Removal Systems

Abstract: The application of enhanced biological phosphorus removal (EBPR) in wastewater treatment plants (WWTPs) has commonly been utilized worldwide. However, the optimum efficiency has not been realized over the past decades, prompting many studies and publications. The limitations, especially comprehension of the abundance and actual potential of polyphosphate-accumulating organisms (PAOs), are not fully understood. Recently identified putative PAOs, Tetrasphaera, present a vast metabolic versatility compared to Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…However, Tetrasphaera has been shown to have the capacity for anaerobic P release; it is also capable of anaerobic P uptake using the energy generated from the fermentation of various organic compounds [ 50 ]. It has been reported that Tetrasphaera can ferment glucose and amino acids to produce acetate, succinate, lactate, and ethanol [ [51] , [52] , [53] ]. Additionally, Ca.…”
Section: Metabolic Diversity Of Paosmentioning
confidence: 99%
“…However, Tetrasphaera has been shown to have the capacity for anaerobic P release; it is also capable of anaerobic P uptake using the energy generated from the fermentation of various organic compounds [ 50 ]. It has been reported that Tetrasphaera can ferment glucose and amino acids to produce acetate, succinate, lactate, and ethanol [ [51] , [52] , [53] ]. Additionally, Ca.…”
Section: Metabolic Diversity Of Paosmentioning
confidence: 99%